1987
DOI: 10.1007/bf01656402
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional support in the management of critically ill patients in surgical intensive care

Abstract: Nutritional support is given to many patients in surgical intensive care after major trauma and serious sepsis but rarely after major elective surgery. We have quantified the changes in body composition that occur in these patients and have found that serious losses of body protein still occur after trauma and sepsis despite nutritional support. Correct nutritional management of critically ill patients in surgical intensive care depends on an understanding of the underlying physiology, drainage of sepsis, a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…A more recent and detailed study performed in 1993 and 1994 [12] confirmed the extent of early posttrauma body composition changes reported previously [20]. The absolute values of the changes were remarkably similar in both studies.…”
Section: Elective Surgerysupporting
confidence: 87%
“…A more recent and detailed study performed in 1993 and 1994 [12] confirmed the extent of early posttrauma body composition changes reported previously [20]. The absolute values of the changes were remarkably similar in both studies.…”
Section: Elective Surgerysupporting
confidence: 87%
“…Even when large amounts of carbohydrate, fat and protein or amino acids are supplied, loss of lean body mass of septic patients is difficult to prevent [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…2 Increased production of glucagon, insulin, cortisol, catecholamines, vasopressin and aldosterone results in a profound change in protein and energy metabolism. 3 Without adequate nutritional support the energy requirements of these patients are primarily met by the breakdown of body proteins with a consequent loss of lean body mass. 4 These metabolic changes are clinically manifested by delayed healing, wound infection and prolonged rehabilitation.…”
Section: Discussionmentioning
confidence: 99%